Evaluasi Pembelajaran Pendidikan Agama Islam Di SMA Negeri Se Kota Palangka Raya - Supriadi, Gito (Jurnal Studi Agama dan Masyarakat, 2009)
The purpose of the study is to describe teaching learning process of the Islamic Education subject in all state senior high schools inPalangkaRayaCity. There is the primary problem in this study, how are the implementation of teaching learning process of the Islamic Education subject in all state senior high schools inPalangkaRayaCity?The subjects of the study were the Islamic education teachers that amounted 11 people. The instrument of data collection were used observation and documentation. Data analysis of this study used quantitative descriptive byÂ  asissted SPSS program version 12.0 and microsof excel.The findings showed that: (1) Teaching learning process of the Islamic Education subject at SMAN 2 Pahandut was good category. It was based on the result of observation got score of 73,53. It was in 50-75 interval mark. (2) Teaching learning process of Islamic education subject at SMAN 2 Pahandut was good category. This was based on getting of teaching score that was done by teacher. It scored of 69,07. (3) Teaching learning process of the Islamic Education subject at SMAN 2 Jekan Raya was very good category. It was based on getting score of 76,47. (4) Teaching learning process of the Islamic Education subject at SMAN 3 Jekan Raya was very good category. It could be seen from getting score of 77,94. It was in 75-100 interval mark.